Immunogenicity and protective efficacy of the recombinant Pasteurella multocida lipoproteins VacJ and PlpE, and outer membrane protein H from P. multocida A:1 in ducks - Li, Yajuan; Xiao, Junfang; Chang, Yung-Fu; Zhang, Hui; Teng, Yutao; Lin, Wencheng; Li, Hongxin; Chen, Weiguo; Zhang, Xinheng; Xie, Qingmei (Frontiers in Immunology, 2022)
Duck cholera (duck hemorrhagic septicemia) is a highly contagious disease caused by Pasteurella multocida, and is one of the major bacterial diseases currently affecting the duck industry. Type A is the predominant pathogenic serotype. In this study, the genes encoding the lipoproteins VacJ, PlpE and the outer membrane protein OmpH of P. multocida strain PMWSG-4 were cloned and expressed as fusion proteins in E. coli. The recombinant VacJ (84.4 kDa), PlpE (94.8 kDa) and OmpH (96.7 kDa) fusion proteins were purified, and subunit vaccines were formulated with a single oil-coated adjuvant, while killed vaccines were prepared using a single oil-coated adjuvant. Antibody responses in ducks vaccinated with recombinant VacJ, PlpE and OmpH proteins formulated with adjuvants were significantly antigenic (p<0.005). Protectivity of the vaccines was evaluated via the intraperitoneal challenge of duck with 20 LD50 of P. multocida A: 1. The vaccine formulation consisting of rVacJ, rPlpE, rOmpH and adjuvant provided 33.3%, 83.33%, and 83.33% protection, respectively, the vaccine formulation consisting of three recombinant proteins, rVacJ, rPlpE, rOmpH and adjuvant, was 100% protective, and the killed vaccine was 50% protective. It was shown through histopathological examination and tissue bacterial load detection that all vaccines could reduce tissue damage and bacterial colonization to a certain extent (p<0.001). These findings indicated that recombinant PlpE or OmpH fusion proteins formulated with oil adjuvant have the potential to be used as vaccine candidates against duck cholera subunits.